Kikuchi-Fujimoto Disease, the Masquerading Menace: A Rare Case Report - Kataria, Rohit (Indian J Dermatol, 2016)
Kikuchi-Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis is a rare, benign, self-limiting disease with unknown etiology characterized by regional lymphadenopathy. A 30-year-old female presented with fever, weakness, multiple joint pain, oral ulcers, erythematous facial rashes, hemorrhagic crusting on both lips, and cervical lymphadenopathy of 2-month duration. Clinically, the disease was mimicking systemic lupus erythematosus, but immunofluorescence was negative for it. Lymph node biopsy suggested a diagnosis of KFD.